Endocrine disorders in Rett syndrome: a systematic review of the literature - Pepe, Giorgia; Coco, Roberto; Corica, Domenico; Luppino, Giovanni; Morabito, Letteria Anna; Lugarà, Cecilia; Abbate, Tiziana; Zirilli, Giuseppina; Aversa, Tommaso; Stagi, Stefano; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2024)
Background: Rett syndrome (RTT) is an X-linked progressive neurodevelopmental disorder that involves mainly girls and is the second most frequent cause of genetic intellectual disability. RTT leads to neurological regression between 6 and 18 months of life and could be associated with a variable neurological impairment. However, RTT affects not only neurological function but also wide aspects of non-neurological organs. Recent data showed that the endocrine system is often involved in RTT patients, including disorders of growth, bone health, thyroid, puberty onset, and weight abnormalities However, systematic data on endocrinopathies in RTT are scarce and limited.Objective: This review aims to analyze the prevalence and type of endocrine comorbidities in RTT population, to allow a precocious diagnosis and appropriate endocrinological management.Methods: Systematic research was carried out from January 2000 to March 2024 through MEDLINE via PubMed, Scopus, and the Cochrane Library.Results: After the selection phase, a total of 22 studies (1090 screened) met the inclusion criteria and were reported in the present review. Five studies were observational-retrospective, four were crosssectional and case report or series, three were survey, prospective, and case-control, and finally one study for descriptive-transversal and longitudinal population-based study. The sample population consisted of multiethnic groups or single ethnic groups. The main endocrinopathies reported were malnutrition, bone alterations, and alterations of puberty onset.Our analysis shows that endocrinopathies are not rare in RTT patients. Therefore, in the context of a multidisciplinary approach, accurate screening and monitoring for endocrinopathies should be recommended in all RTT patients, to improve clinical practice, healthcare management, and, finally, patients' quality of life.